'X is the odd one out, because the other two are more about the farmland' – Dutch L1 student teachers' struggles to reason about grammar in odd one out tasks. (September 2021) - van Rijt, Jimmy H.M.; Hulshof, Hans; Coppen, Peter-Arno J.M.
Highlights: Dutch language student teachers have difficulty reasoning about grammar. Student teachers do not outperform 14 year old pre-university students on grammatical reasoning. Student teachers show several signs of conceptual confusion for basic grammatical categories. Student teachers' level of grammatical understanding can predict their reasoning ability. The elaborateness of their reasoning also predicts their reasoning ability. Abstract: Grammatical knowledge is an important part of L1 language education. Nevertheless, teachers find it challenging to convey an in-depth understanding of grammar to their students. Previous research suggests that understanding might be stimulated by focusing on grammatical reasoning. The current mixed-methods study explores the grammatical reasoning of 108 Dutch L1 student teachers' in odd one out tasks, showing that student teachers struggle with such reasoning tasks. A multilevel regression analysis indicates that their level of grammatical understanding as measured by a Test of Grammatical Understanding (TGU) and the elaborateness of student teachers' argumentation significantly predict the quality of their grammatical reasoning. Student teachers' performances were also compared to 14 year old pre-university students' performances (N = 120). Contrary to what was hypothesized, senior student teachers did not manage to outperform junior student teachers, nor did student teachers outperform pre-university students. The paper discusses plausible reasons for these findings and explores how teacher education might need to shift focus to better develop student teachers' grammatical reasoning skills.